Transformation of Traditional Learning to Digital Learning - Rifelino Rifelino; Ambiyar Ambiyar; Nurhasan Syah; Syahril Syahril (Edumaspul: Jurnal Pendidikan, 2022)
The outbreak of the Coronavirus disease (Covid-19) since the end of 2019 until its peak in the first quarter of 2022 changed the pattern of Indonesian education. The interfaces of Traditional learning between educators and students directly switched to digital learning. This study aims to describe the transformation of offline learning phenomena into digital learning as a representation of online learning. Various references consisting of journals, articles, and books are used as secondary data in collecting scientific data. The results of the study show that there is technological adaptation among the people by using various types of platforms, such as: google meet, google classroom, zoom, LMS (Learning Management System). The pandemic condition has triggered people to become tech-savvy, thus shifting traditional learning patterns to digital (online).